B, N, Fe and O multi-element co-doped porous carbon-based material

The preparation of B, N, Fe, O multivariate co-doped porous carbon-based materials through one-step carbonization method is solved, and the problem of insufficient performance of traditional carbon-based materials in electrochemical energy storage equipment is achieved, and high-performance electrochemical storage and conversion effects are achieved.

CN119706803APending Publication Date: 2025-03-28FUZHOU UNIV

Patent Information

Application Number
CN202411942084.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing carbon-based materials have problems such as electrochemical energy storage equipment such as supercapacitors and sodium ion batteries, such as surfaces, poor hydrophilicity, limited electrochemical active sites, and low charge storage capacity, which makes it difficult for their performance to meet the requirements of high-performance energy storage equipment.

Method used

By adopting a one-step carbonization method, water-soluble sugar compounds and water-soluble iron salts are used as carbon sources and ferrite sources, dimethylaminoborane and the like are added as boron nitrogen sources, B, N, Fe, and O multi-compartmental co-doped porous carbon-based materials are prepared.

Benefits of technology

The prepared porous carbon material has a graded porous structure and rich electrochemical active sites, exhibits excellent electrochemical properties, can achieve high power density and high energy density, and is suitable for supercapacitors and sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706803A_ABST
    Figure CN119706803A_ABST
Patent Text Reader

Abstract

The invention discloses a B, N, Fe and O multi-element co-doped porous carbon-based material as well as a preparation method and application thereof. The preparation method comprises the following steps: dissolving a water-soluble carbohydrate and a water-soluble ferric salt in deionized water according to a certain ratio, adding dimethylamino borane and the like as a boron-nitrogen source, uniformly mixing under the ultrasonic action, and drying to form a carbon precursor compound; and placing the dried carbon precursor compound in a vacuum furnace for high-temperature carbonization to obtain the B, N, Fe and O multi-element co-doped porous carbon-based material. Iron salt, dimethylaminoborane and the like are respectively used as multi-element doping sources and pore-forming is carried out on the carbon matrix at the same time, so that a hierarchical pore structure is obtained. The multi-element co-doped porous carbon-based material with a hierarchical pore structure is constructed by adopting a simple method, abundant electrochemical active sites can be provided by doping multiple heteroatoms, and the electrochemical performance of a carbon matrix is improved. The material can be applied to supercapacitor electrodes and sodium ion battery materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of carbon material preparation, and in particular relates to a B, N, Fe, O multi-component co-doped porous carbon-based material and a preparation method and application thereof. Background Art

[0002] As the global energy crisis and environmental problems become increasingly severe, the development of high-performance energy storage materials has become a hot topic in current scientific research. Electrochemical energy storage and conversion devices such as supercapacitors, sodium-ion batteries and fuel cells have received widespread attention due to their high energy density, long cycle life and fast charge and discharge characteristics.

[0003] The main components of supercapacitors include electrode materials, electrolytes, diaphragms and current collectors, among which electrode materials are the core factor affecting their performance. Electrode materials largely determine the energy storage capacity and working efficiency of supercapacitors, and are the key to improving their electrochemical performance. There are many types of electrode materials, mainly porous carbon-based materials, conductive polymers, transition metal oxides, etc. Among them, porous carbon-based materials have attracted the attention of many researchers due to their wide source of raw materials, diverse types, low cost, simple synthesis methods, good conductivity, stable chemical properties, good electrochemical performance and cycle stability.

[0004] There are many types of carbon materials, such as porous carbon, graphene, carbon fiber, etc. Porous carbon-based materials are ideal electrode materials due to their high specific surface area, good conductivity, structural adjustability and chemical stability. However, in practical applications, traditional porous carbon materials have problems such as lack of surface functional groups, poor hydrophilicity, limited electrochemical active sites, and low charge storage capacity, which makes it difficult for their specific capacitance and energy density to meet the requirements of high-performance energy storage devices.

[0005] CN115240988 A discloses a doped carbon material for supercapacitors and its preparation method and application. The method of the present invention adopts a two-step method to oxidize coal into a carbon point solution with extremely rich surface oxygen-containing functional groups, then introduces boron and nitrogen heteroatoms, and finally carbonizes and solidifies to obtain a boron-nitrogen doped carbon material. However, this method requires the addition of a nitrogen source and a boron source separately, the process is relatively complicated, the types of raw materials added are relatively large, the steps are cumbersome, and strong acids and strong oxidants need to be used in the preparation process, which is dangerous, causes pollution to the environment, and has high requirements for process operation.

[0006] Luo et al. prepared B / N co-doped biomass porous carbon supercapacitor electrode materials by carbonization, activation and hydrothermal processes. It has a good specific capacitance value at a current density of 1A / g, but its process is relatively more complicated, the heteroatom doping amount is low and a strong acid reagent is required. (Luo L, Luo LC, Deng JP, et al. High performance supercapacitor electrodes based on B / N Co-doped biomass porous carbonmaterials by KOH activation and hydrothermal treatment [J]. International Journal of Hydrogen Energy, 2021, 46(63): 31927-31937.) Combined with the above research and analysis, it is found that the current modification of carbon-based materials has problems such as complex process, easy to pollute the environment, high cost, and unsuitable for large-scale production. Heteroatom doping can not only perform secondary pore formation on the surface of carbon materials, but also increase its functional group content, improve wettability, and generate additional pseudocapacitance. The present invention uses widely available water-soluble sugar compounds as carbon sources, water-soluble iron salts as iron and oxygen sources, dimethylamino borane and the like as boron and nitrogen sources, and adopts a one-step carbonization method to prepare B, N, Fe, O multi-component co-doped porous carbon-based materials. The experimental operation is relatively simple, with high feasibility and low cost. Summary of the invention

[0007] The purpose of the present invention is to provide a B, N, Fe, O multi-element co-doped porous carbon-based material, which is prepared by a simple one-step carbonization method. The prepared porous carbon has a hierarchical porous structure and abundant electrochemical active sites, exhibits excellent electrochemical properties, and can be used as a supercapacitor electrode and sodium ion battery material with high power density and high energy density.

[0008] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a B, N, Fe, O multi-component co-doped porous carbon-based material, comprising the following steps: (1) Take a certain mass ratio of a water-soluble sugar compound and a water-soluble iron salt, dissolve them in deionized water to form a uniform solution; (2) adding a certain amount of boron and nitrogen source to the mixed solution in step (1) and ultrasonicating for 5 to 60 minutes; (3) The mixed solution of step (2) is transferred to a vacuum drying oven for reaction and drying to form a porous carbon precursor, which is then ground into powder; (4) The porous carbon precursor powder obtained in step (3) is placed in a vacuum hot pressing sintering furnace for carbonization. The carbonized product is fully ground in a ball mill for 2 to 6 hours to obtain a B, N, Fe, O multi-element co-doped porous carbon-based material. Preferably: The water-soluble sugar compound described in step (1) is any one of sucrose, glucose, fructose, and chitosan, the water-soluble iron salt is any one of ferrous sulfate heptahydrate, ferric nitrate nonahydrate, and ferric chloride hexahydrate, and the mass ratio of the water-soluble sugar compound to the water-soluble iron salt is 1:1 to 1:4; In step (2), the boron and nitrogen source is any one of dimethylamino borane and ammonium borate; the mass of the boron and nitrogen source such as dimethylamino borane is 5% to 40% of the mass of the carbohydrate compound.

[0009] The reaction temperature of step (3) is 80-120° C. and the reaction time is 6-12 h.

[0010] In step (4), the carbonization temperature is 700-1200° C., the heating rate is 1-6° C. / min, and the carbonization time is 1-4 h.

[0011] As mentioned above, the application of B, N, Fe, and O multi-co-doped porous carbon-based materials is used for electrode materials of supercapacitors and negative electrode materials of sodium ion batteries. In addition, multi-heteroatom doping makes it also show certain application potential in fields such as electrocatalysis.

[0012] The beneficial effects of the present invention are: (1) The present invention uses cheap water-soluble sugar compounds as carbon sources, mixes them with water-soluble iron salts, and then adds boron and nitrogen sources such as dimethylamino borane. After uniform mixing, a porous carbon-based material with B, N, Fe, and O multi-element co-doping is prepared by one-step carbonization. The doping of multiple elements of B, N, Fe, and O does not require complicated procedures. Iron salts and boron and nitrogen sources such as dimethylamino borane that are also water-soluble are added to the carbon material precursor, and multi-element co-doping can be achieved by one-step carbonization. At the same time, the substitution process of heteroatoms consumes part of the carbon atoms, thereby obtaining a hierarchical porous carbon material with B, N, Fe, and O multi-element co-doping.

[0013] (2) The present invention adds a substance to achieve dual doping of two elements, which does not require multiple subsequent processing, and the process flow is simpler. At the same time, the porous carbon-based material obtained has a fluffy and porous surface and a uniform structure. The preparation process does not use strong acids, strong bases and strong oxidants that are easy to pollute the environment, which is environmentally friendly; there are fewer steps, the doping amount of heteroatoms is easy to control, the reaction equipment is simple, the reaction conditions are easy to achieve, and it is easy to prepare for industrial production.

[0014] (3) EDS shows that B, N, Fe, and O are successfully doped into the porous carbon in the B, N, Fe, and O multi-element co-doped porous carbon-based material prepared by the method of the present invention. XPS analysis and fitting show that the doping amount of B is 5.01%, the doping amount of N is 5.4%, the doping amount of O is 15.2%, and the doping amount of Fe is 4.89%.

[0015] (4) The B, N, Fe, O multi-element co-doped porous carbon-based material prepared by the present invention has a stable hierarchical porous structure. The four elements are doped to introduce a large number of heteroatoms and active sites, which is beneficial to improve the specific capacitance, cycle stability and coulombic efficiency of the porous carbon. Good electrochemical performance and multi-element co-doping enable it to achieve more diversified applications, showing great application potential in the fields of supercapacitor electrodes, sodium ion battery electrodes and electrocatalytic electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is the EDS image of the B, N, Fe, O multi-co-doped porous carbon-based material prepared in Example 1 of the present invention.

[0017] Figure 2 This is the SEM image of the B, N, Fe, O multi-co-doped porous carbon-based material prepared in Example 2 of the present invention.

[0018] Figure 3 This is the XPS graph of the B, N, Fe, O multi-co-doped porous carbon-based material prepared in Example 3 of the present invention.

[0019] Figure 4 This is a cyclic voltammogram of the B, N, Fe, O multi-co-doped porous carbon-based material prepared in Example 4 of the present invention.

[0020] Figure 5 This is a constant current charge and discharge curve of the B, N, Fe, O multi-co-doped porous carbon-based material prepared in Example 5 of the present invention.

[0021] Figure 6 This is a diagram of the cycle performance and coulombic efficiency of the B, N, Fe, O multi-co-doped porous carbon-based material prepared in Example 6 of the present invention.

[0022] Figure 7 This is a digital photograph of a light bulb lit after the B, N, Fe, O multi-component co-doped porous carbon-based material prepared in Examples 1-6 of the present invention was assembled into a button battery. DETAILED DESCRIPTION

[0023] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0024] Example 1 Take 3g sucrose and 3g ferrous sulfate heptahydrate and dissolve them in 50mL deionized water and mix them evenly. Then add 0.3g dimethylamino borane, place the beaker in an ultrasonic machine for 30 min to mix the raw materials thoroughly, then put it in an oven and fully dry it at 80°C to form a carbon precursor. Pour the dried and ground carbon precursor into a graphite crucible, place it in a vacuum hot pressing sintering furnace, heat it to 800°C at a heating rate of 2°C / min, and keep it carbonized in a vacuum environment for 2 h. The obtained carbonized product is fully ground in a ball mill for 1 h to obtain a B, N, Fe, O multi-electrode co-doped porous carbon-based material. Using a three-electrode system, 6 mol / L KOH solution as the electrolyte, and 1 A / g, the specific capacitance is measured to be 314.2F / g.

[0025] Example 2 Take 3g sucrose and 3g ferrous sulfate heptahydrate and dissolve them in 50mL deionized water and mix them evenly. Then add 0.6g dimethylamino borane, place the beaker in an ultrasonic machine for 30 minutes to mix the raw materials thoroughly, and then put it in an oven and fully dry it at 90℃ to form a carbon precursor. Pour the dried and ground carbon precursor into a graphite crucible, place it in a vacuum hot pressing sintering furnace, heat it to 1000℃ at a heating rate of 2℃ / min, and keep it carbonized in a vacuum environment for 2 hours. The obtained carbonized product is fully ground in a ball mill for 1 hour to obtain a B, N, Fe, O multi-electrode co-doped porous carbon-based material. Using a three-electrode system, 6 mol / L KOH solution as the electrolyte, and 1 A / g, the specific capacitance is measured to be 300.7F / g.

[0026] The SEM image of the B, N, Fe, O multi-component co-doped porous carbon-based material prepared in this embodiment is shown in FIG. Figure 2 As shown by Figure 2 It can be seen that there is a fluffy porous structure on the surface of the material, and there are many tiny particles (containing iron, boron and other compounds) embedded in the pores, which greatly improves its electrochemical properties. Compared with single boron-nitrogen dual doping or nitrogen-oxygen dual doping, it has better electrochemical performance.

[0027] CN 115240988 B reports a doped carbon material for supercapacitors and its preparation method and application. After processing anthracite, 15 ml of 20% ammonia water was used as a nitrogen source and 2 g of boric acid was used as a boron source to prepare a coal-based boron-nitrogen co-doped carbon material. The specific capacitance was measured to be 221.3 F / g at a current density of 1 A / g. CN105575673 B reports a preparation method and application of a porous carbon electrode material doped with nitrogen and oxygen in situ. After pre-carbonizing cattle bones at 400 ° C, they were ground and mixed with KOH in a mass ratio of 1:2, and then placed in a nitrogen atmosphere and heated to 800 ° C for 2 hours. The obtained activated carbonization product was then stirred and pickled in a 2 mol / L nitric acid solution for 12 hours, and after washing and drying, a porous carbon material co-doped with nitrogen and oxygen was obtained. The specific capacitance was measured to be 201.8 F / g at a current density of 1 A / g. The above two doping methods both improve the electrochemical properties of porous carbon substrates, but their preparation processes are cumbersome and easily corrode equipment, which is not conducive to large-scale production. In addition, the electrochemical performance of the obtained binary doped porous carbon-based materials is lower than that of the multi-co-doped porous carbon-based materials reported in this application.

[0028] Example 3 Take 3g of chitosan and 9g of ferric chloride hexahydrate and dissolve them in 50mL of deionized water and mix them evenly. Then add 0.45g of dimethylaminoborane and place the beaker in an ultrasonic machine for 30 minutes to mix the raw materials thoroughly. Then put it in an oven and dry it thoroughly at 90°C to form a carbon precursor. Pour the dried and ground carbon precursor into a graphite crucible, place it in a vacuum hot pressing sintering furnace, heat it to 1000°C at a heating rate of 3°C / min, and carbonize it in a vacuum environment for 2 hours. Grind the obtained carbonized product in a ball mill for 1 hour to obtain a B, N, Fe, and O multi-co-doped porous carbon-based material. The XPS graph of the B, N, Fe, and O multi-co-doped porous carbon-based material prepared in this embodiment is shown in the figure. Figure 3 shown.

[0029] Example 4 Take 3g of glucose and 3g of ferrous sulfate heptahydrate and dissolve them in 50mL of deionized water and mix them evenly. Then add 0.6g of dimethylamino borane, place the beaker in an ultrasonic machine for 30 minutes to mix the raw materials thoroughly, and then put it in an oven and fully dry it at 90°C to form a carbon precursor. Pour the dried and ground carbon precursor into a graphite crucible, place it in a vacuum hot pressing sintering furnace, heat it to 900°C at a heating rate of 2°C / min, and keep it carbonized in a vacuum environment for 1 hour. The obtained carbonized product is fully ground in a ball mill for 1 hour to obtain a B, N, Fe, O multi-co-doped porous carbon-based material.

[0030] The cyclic voltammetry curve of the B, N, Fe, O multi-element co-doped porous carbon-based material prepared in this embodiment is as follows: Figure 4As shown by Figure 4 It can be seen that the change in scanning rate has little effect on the shape of its CV curve, indicating that the material has good rate performance and stability.

[0031] Example 5 Take 3g of glucose and 6g of ferric nitrate nonahydrate and dissolve them in 50mL of deionized water and mix them evenly. Then add 0.9g of dimethylamino borane, place the beaker in an ultrasonic machine for 60 min to mix the raw materials thoroughly, and then put it in an oven and fully dry it at 90°C to form a carbon precursor. Pour the dried and ground carbon precursor into a graphite crucible, place it in a vacuum hot pressing sintering furnace, heat it to 1100°C at a heating rate of 5°C / min, and keep it in a vacuum environment for carbonization for 2 h. The obtained carbonized product is fully ground in a ball mill for 1 h to obtain a B, N, Fe, O multi-co-doped porous carbon-based material.

[0032] Example 6 Take 3g of fructose and 6g of ferric chloride hexahydrate and dissolve them in 50mL of deionized water and mix them evenly. Then add 0.3g of ammonium borate and place the beaker in an ultrasonic machine for 60 minutes to mix the raw materials thoroughly. Then put it in an oven and fully dry it at 90°C to form a carbon precursor. Pour the dried and ground carbon precursor into a graphite crucible, place it in a vacuum hot pressing sintering furnace, heat it to 1100°C at a heating rate of 2°C / min, and maintain carbonization in a vacuum environment for 2 hours. Grind the obtained carbonized product in a ball mill for 1 hour to obtain a B, N, Fe, and O multi-co-doped porous carbon-based material. The cycle performance and coulomb efficiency diagram of the B, N, Fe, and O multi-co-doped porous carbon-based material prepared in this embodiment are shown in the following figure. Figure 6 As shown by Figure 6 It can be seen that after 5000 cycles of charge and discharge, the specific capacitance retention rate reaches 88.9%, and the coulombic efficiency is close to 100%, which proves that the material has good charge and discharge characteristics and cycle stability.

[0033] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing a B, N, Fe, O multi-component co-doped porous carbon-based material, characterized in that: The specific steps are: (1) dissolving a water-soluble sugar compound and a water-soluble iron salt in deionized water to form a uniform mixed solution; (2) adding the boron nitrogen source to the mixed solution of step (1), ultrasonically mixing for 5 to 60 minutes, and mixing evenly; (3) vacuum drying the uniformly mixed solution in step (2) to form a solid carbon precursor, and grinding the solid carbon precursor into a powder; (4) The carbon precursor powder of step (3) is subjected to vacuum hot pressing sintering to carbonize it. The carbonized product is fully ground for 2 to 6 hours to obtain the B, N, Fe, O multi-element co-doped porous carbon-based material.

2. The preparation method according to claim 1, characterized in that: The water-soluble sugar compound described in step (1) is one of sucrose, glucose, fructose, and chitosan; the water-soluble iron salt is one of ferrous sulfate heptahydrate, ferric nitrate nonahydrate, and ferric chloride hexahydrate; and the mass ratio of the sugar compound to the iron salt is 1:1 to 1:

4.

3. The preparation method according to claim 1, characterized in that: The boron and nitrogen source described in step (2) is dimethylamino borane or ammonium borate, and the mass of the boron and nitrogen source is 5% to 40% of the mass of the water-soluble sugar compound.

4. The preparation method according to claim 1, characterized in that: In step (3), the drying temperature is 80 to 120° C. and the drying time is 6 to 12 hours.

5. The preparation method according to claim 1, characterized in that: In step (4), the carbonization temperature is 700-1200° C., the heating rate is 1-6° C. / min, and the carbonization time is 1-4 h.

6. A B, N, Fe, O multi-component co-doped porous carbon-based material prepared by the method according to any one of claims 1 to 5.

7. An application of a B, N, Fe, O multi-component co-doped porous carbon-based material prepared by the method according to any one of claims 1 to 5, characterized in that: The B, N, Fe, O multi-component co-doped porous carbon-based material is used as an electrode material for a supercapacitor or a sodium ion battery material.

Citation Information

Patent Citations

  • Preparation method and application of a nitrogen and oxygen in-situ doped porous carbon electrode material

    CN105575673B

  • A doped carbon material for supercapacitors, its preparation method and application

    CN115240988B

Cited By

  • A ternary doped porous carbon composite material, a preparation method and application thereof

    CN122889601A